Joint Torque Calculation of Compression Sports Spats using Anisotropic Hyperelastic Model. (2016) - Aoki, Hitoshi; Shimana, Takatsugu; Sato, Hiroki; Yabuki, Ryuma; Matsuda, Akihiro
Abstract: In this study, a numerical design method for high-performance sports spats was proposed. The effect of sports spats on the human body during running motions was calculated. An anisotropic hyperelastic model considering stress softening was implemented to reproduce the mechanical characteristics of the sports spats fabric. Also, cyclic tensile loading tests were conducted to evaluate the mechanical characteristics of the sports spats fabric, which was composed of tricot fiber. The stiffness changed with loading direction, and the stiffness was softened depending on previous maximum stretch. The material parameters of the sports spats were identified using the cyclic loading test results. The theoretical calculations showed good agreement with experimental results. The anisotropic hyperelastic model was applied to a 3D-CG human model and running motion data were also introduced into the human model. The proposed numerical design method enabled calculation of the stress induced by the sports spats during running motions. Also, the joint torque generated in each knee was calculated using the stress calculation. The effect of high-performance sports spats on the human body was thus evaluated numerically.